1998
DOI: 10.1037/0022-3514.75.3.589
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype efficiency reconsidered: Encoding flexibility under cognitive load.

Abstract: According to the encoding flexibility model, stereotypes are efficient because they facilitate, in different ways, the encoding of both stereotype-consistent and stereotype-inconsistent information when capacity is low. Because stereotypical information is conceptually fluent, it may be easily understood, even when resources are scant. As a result, processing resources may shift from stereotypical toward counterstereotypical information, which is difficult to comprehend under such conditions. Thus, whereas inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
257
2
11

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 220 publications
(296 citation statements)
references
References 82 publications
22
257
2
11
Order By: Relevance
“…Consistent with this characterization, stereotypes have been found to be especially likely to guide social perception when processing capacity is low (e.g., for reviews, see Fiske, 1998;Hamilton & Sherman, 1994;Hilton & von Hippel, 1996;Sherman, Macrae, & Bodenhausen, 2000). With respect to intentional inferences, Sherman, Lee, Bessenoff, and Frost (1998;see also Sherman & Frost, 2000) demonstrated that when resources were low, perceivers were particularly likely to extract the conceptual gist (trait meanings) from consistent but not inconsistent behaviors in an intentional impression formation task. In contrast, when cognitive resources were high, both types of behaviors were understood equally well.…”
Section: Stereotypical Inferences 293mentioning
confidence: 74%
See 2 more Smart Citations
“…Consistent with this characterization, stereotypes have been found to be especially likely to guide social perception when processing capacity is low (e.g., for reviews, see Fiske, 1998;Hamilton & Sherman, 1994;Hilton & von Hippel, 1996;Sherman, Macrae, & Bodenhausen, 2000). With respect to intentional inferences, Sherman, Lee, Bessenoff, and Frost (1998;see also Sherman & Frost, 2000) demonstrated that when resources were low, perceivers were particularly likely to extract the conceptual gist (trait meanings) from consistent but not inconsistent behaviors in an intentional impression formation task. In contrast, when cognitive resources were high, both types of behaviors were understood equally well.…”
Section: Stereotypical Inferences 293mentioning
confidence: 74%
“…Prior research has also shown that traits are more likely to be inferred spontaneously from stereotype-consistent than stereotype-inconsistent behaviors (e.g., Wigboldus et al, 2003). Finally, when explicitly attempting to form an impression of another person, perceivers under a cognitive load have been shown to be more likely to extract the gist meaning of consistent rather than inconsistent behaviors (Sherman et al, 1998). The present results extend these findings by demonstrating that stereotypes are especially likely to affect the extent to which traits are spontaneously inferred from behaviors when processing capacity is depleted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four pairs of items included one common trait and one rare trait behavior performed by different members of Group A, and four pairs of items included one common trait and one rare trait behavior performed by different members of Group B. For each pair, the two behaviors were presented for a total of 5 s. Previous research has indicated that this is insufficient time to process both behaviors fully (Sherman, Lee, Bessenoff, & Frost, 1998), thereby placing pressure on participants to selectively attend to one item or the other. During the presentation of each pair of behaviors, the X would appear on the same side of the screen as either the common trait or rare trait behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Nesta segunda situação têm-se utilizado os atributos para avaliar a estereotipicalidade de diferentes tipos de julgamentos (e.g., Gilbert & Hixon, 1991;Plant & Devine, 1998) e/ou mensurar o grau de acessibilidade ou de activação dos estereótipos (e.g., Macrae, Bodenhausen, Milne, & Jetten, 1994;Kawakami, Dovidio, Moll, Hermsen, & Russin, 2000) e, ainda, para caracterizar o processamento da informação estereotípica e a sua codificação em memória (e.g., Macrae, Stangor, & Milne, 1994;Macrae, Bodenhausen, Milne, & Ford, 1997). Em medidas de memória diferencial para esses atributos, tem sido possível caracterizar os processos de codificação e/ou recuperação da informação estereotípica, quer através de recordação livre (Experiência 3, Macrae, Stangor, & Milne, 1994;Macrae et al, 1997), quer de reconhecimento (Sherman, Lee, Bessenoff, & Frost, 1998). Por sua vez, os atributos incorporados em medidas de acessibilidade dos estereótipos podem constituir palavras a serem reconhecidas numa matriz de letras tipo sopa de letras (e.g., Experiência 2, Macrae, Stangor, & Milne, 1994), palavras fragmentadas a serem completadas pelos participantes (e.g., Gilbert & Hixon, 1991), palavras cujo tempo de leitura/pronunciação varia consoante o estereótipo está ou não activado (e.g., Moskowitz, Gollwitzer, Wasel, & Shaal, 1999) ou, ainda, palavras incorporadas em tarefas de decisão lexical (e.g., Macrae, Bodenhausen, Milne, & Jetten, 1994;Wittenbrink, Judd, & Park, 1997).…”
Section: Operacionalização Do "Estereótipo"unclassified